Integration of Local Wisdom Values in Realizing Good Nagari Governance - Muhammad Fachri Adnan; Syamsir Syamsir; Zikri Alhadi; Hasbullah Malau; Annisa Vira Widesma; Karjuni Dt. Maani (JURNAL ILMU SOSIAL, 2022)
This research began with the issue that the implementation of Nagari governance in West Sumatra Province was not in accordance with the principles of good local governance based on the philosophy of local wisdom, particularly in the Minangkabau community. The purpose of this study is to explain the integration of local wisdom values, namely the leadership of the Tigo Tungku Sajarangan, the cooperation, and the consensus agreement in realizing the principles of good governance in the Nagari government in West Sumatra. The research was conducted in three villages, namely Nagari Limo Kaum in Tanah Datar Regency, Nagari Kamang Mudiak in Agam Regency, and Nagari Kayu Tanam in Padang Pariaman Regency. The data was collected using the methods of interview techniques, documentation studies, and Focus Group Discussions (FGD). The data validity test was carried out by source triangulation and method triangulation. The data were analyzed using qualitative analysis techniques through three stages, namely reduction and selection, interpretation, and inference. The results showed that the values of Tigo Tungku Sajarangan leadership, consensus agreement, and cooperation could be integrated into realizing the principles of good governance in the Nagari government in West Sumatra.